Analisis Kualitas Pelayanan Publik Terhadap Kepuasan Pasien Di Puskesmas Sleman, Kapanewon Sleman, Daerah Istimewa Yogyakarta - Handayani, Melia Dwi; Faidati, Nur (Indonesian Journal Publisher, 2025)
Health services play a strategic role in ensuring the quality of public services, especially in increasing patient satisfaction. The purpose of this study was to analyze the quality of public services in the registration service section for patient satisfaction at Puskesmas Sleman. This research uses descriptive qualitative method. Informants were selected based on purposive sampling technique, namely the head of the Sleman Health Center, registration officers, and patients. Data collection was done by structured interviews and documentation. Data analysis includes reduction, presentation, and conclusion. The results showed that the quality of service at the Sleman Health Center is quite good, adequate facilities, friendly officers and good empathy and the application of the 3S principle (Smile, Salam, Sapa), services provided according to the SOP, and supported by a digital security system. Supporting factors include officer competence, agency support, and use of technology. The main obstacles are limited waiting space, unstable internet network and low patient digital literacy. The factors that have the most influence on patient satisfaction are empathy, responsiveness, and tangibles